Beneficial Effect of Antibiotics and Microbial Metabolites on Expanded Vδ2Vγ9 T Cells in Hepatocellular Carcinoma Immunotherapy - Han, Jiajia; Zhang, Siya; Xu, Yi; Pang, Yongsheng; Zhang, Xue; Hu, Yu; Chen, Hui; Chen, Wanjun; Zhang, Jianmin; He, Wei (Frontiers in Immunology, 2020)
Animal experiments and clinical trials have shown that the gut microbiota modulates host immunity and immune checkpoint-mediated responses to tumor cells. However, it remains unclear whether microbiota can also play a role in the tumor immune response of γδT cells, a kind of cell that targets cancer directly. Here, we report that microbiota dysbiosis induced by antibiotics enhanced γδT cell efficacy during tumor therapy in a mouse model. Further microbiota and metabolite analysis revealed that the alteration of γδT cell cytotoxicity might be closely associated with specific metabolites, which are produced by intestinal bacteria and stimulate γδT cells to release more cytotoxic cytokines, such as granzyme B and perforin. Among the metabolites that we analyzed, 3-indopropionic acid (IPA) showed the highest concentration in antibiotic-treated mice and can improve the cytotoxic ability of γδT cells both in vitro and in vivo. Our research determined how the gut microbiota can influence the antitumor ability of γδT cells and identified potential intermediate molecules that connect the gut microbiota and γδT cells.